Circ_0002476 regulates cell growth, invasion, and mtDNA damage in non–small cell lung cancer by targeting miR‐1182/TFAM axis. Issue 20 (3rd September 2022) - Wang, Weijie; Sun, Haiting; Ma, Xuan; Zhu, Ting; Zhang, Haina
Abstract: Background: Many circular RNAs (circRNAs) have been identified as potential targets for cancer therapy. However, the role of circ_0002476 in non–small cell lung cancer (NSCLC) progression has not been explored. Methods: The expression levels of circ_0002476, microRNA (miR)‐1182, and mitochondrial transcription factor A (TFAM) were detected by quantitative real‐time polymerase chain reaction. Cell functions were measured by cell counting kit 8 assay, EdU assay, colony formation assay, flow cytometry and transwell assay. Mitochondrial DNA (mtDNA) damage was assessed by measuring mtDNA copy number and transcript levels of ND1 and ATP6. Protein expression was examined by western blot. The interaction between miR‐1182 and circ_0002476 or TFAM was detected by dual‐luciferase reporter assay and RNA pull‐down assay. Animal experiments were performed to explore circ_0002476 role in vivo. Exosomes (Exs) were extracted and identified by transmission electron microscopy and nanoparticle tracking analysis. Results: Circ_0002476 was overexpressed in NSCLC tissues and cells. Circ_0002476 knockdown suppressed NSCLC cell proliferation and invasion, while promoted apoptosis and mtDNA damage. Circ_0002476 could sponge miR‐1182, and miR‐1182 inhibitor reversed the influence induced by circ_0002476 knockdown. Moreover, TFAM was targeted by miR‐1182, and miR‐1182 hindered NSCLC cell progression by regulating TFAM. Additionally, circ_0002476 silencing could reduce NSCLC tumor growth by miR‐1182/TFAM. Further analyzed showed that Exs were involved in the transport of circ_0002476 between cells. Conclusion: Taken together, our findings suggested that circ_0002476 might be a potential molecular target for NSCLC treatment. Abstract : Circ_0002476 could promote proliferation, invasion, suppress apoptosis and mtDNA damage of NSCLC cells in vitro, as well as NSCLC tumor growth in vivo, through miR‐1182/TFAM axis, confirming that it might accelerate the malignant progression of NSCLC.